The Influence of Social Media and Customer Engagement on Competitive Advantage and Marketing Performance of UMKMs in Prigen - Arbiatur Rohmah, Nila; Urwatul Wusko, Any (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to analyze the influence of social media use and customer engagement on competitive advantage and marketing performance in Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Prigen District. This study used a quantitative approach with a survey of 100 MSMEs, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The test results indicate that social media use has a positive and significant effect on competitive advantage (β = 0.623; p < 0.05), and customer engagement has a positive and significant effect on competitive advantage (β = 0.557; p < 0.05). Furthermore, social media use and customer engagement also significantly influence marketing performance. The R² value of 0.557 indicates that competitive advantage and marketing performance can be adequately explained by the research variables. The practical implications of this research demonstrate that this theme emphasizes the importance of social media-based marketing strategies and strengthening customer engagement as an effort to improve the competitive advantage and marketing performance of MSMEs amidst the dynamics of the digital market.